Analisis Budaya Organisasi Sempoa SIP Tc. Resinda Race - Syali Devita Ananda; Uus Mohammad Darul Fadli (CV. ITTC INDONESIA, 2024)
Organizational culture is important in the company, a good organizational culture will help achieve organizational goals. The purpose of this research is to explain the implementation of Organizational Culture in management, innovation, attention to detail, people orientation, team orientation, speed and responsiveness. This research uses a qualitative descriptive method, this research also involves interviews and observations. The interviewees in this study involved 5 employees at the research location at Sempoa SIP Resinda Race. The results of this study are that the company accepts well the ideas given by employees, the company lacks attention to detail in its work, in this company employee welfare needs to be considered so that productivity increases, teamwork carried out needs to be improved again, speed and responsiveness carried out by employees are quite good.